The Muslim Discovery of Europe - Sulayman S. Nyang (International Institute of Islamic Thought, 1985)
Bernard LEWIS, The Muslim Discovery of Europe (New York/London: W.W. Norton & Co., 1982), 350 pp., Index & Illustrations. Price $19.95. The Muslims have had a long history of relations with Western European peoples. Some part of it was tumultous and violent and the other was peaceful and harmonious. It was the Muslims who held the torch of civilization when the lights went out in Europe and elsewhere in the world. And indeed it was the Muslims who passed on to Europe in the Middle Ages the coveted intellectual jewels of the ancient world. However, such transactions and ties between the Western European peoples and the Muslim world have led to two major historical developments. The first was the renaissance in Europe, which interestingly enough led to the distancing of Europe from the Muslim World. The second was the subsequent development of learning and the sciences in Europe and the rise of European power to challenge, threaten, and finally defeat Muslim power in the world. It is indeed against this background that one can examine this book by the well-known but controversial British orientalist, Professor Bernard Lewis. His book is certainly an important contribution to the limited literature on early and medieval Muslim transactions with the European world. But in order to do justice to the work and its author, let us analyze its contents and see how and to what extent the author captures the salient points about the Muslim discovery of the West. The book is divided into twelve chapters with a preface and a note on the source of illustrations. In the first chapter, entitled "Contact and Impact", Professor Lewis traces the rise of Islam in the Middle East and the geopolitical revisions that accompanied the Muslim ascendancy. He points out that at the time the Muslim armies made their sweep over the Mediterranean region Christianity served as the dominant worldview of the area's inhabitants. But within a very short span of time the Muslims were able not only to conquer Christian lands but also to Arabicize and Islamize the hitherto non-Arabic, Christian peoples. Professor Lewis goes on to identify important milestones in Islamic history. Among these milestones four are of great importance. First of all, he talks about the Western perception of the Islamic threat. This was evident in the desperate attempt to check the tide of lslamism in Byzantium and later in the southern part of Western Europe. particularly in the Iberian Peninsula. He brings out an important point ...